1978
DOI: 10.1203/00006450-197804000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Tay-Sachs Disease: Ultrastructural Studies on Cultured Fibroblasts

Abstract: SummaryThe knowledge that the biochemical lesion associated with Tay-Sachs disease is demonstrable in many tissues, and in particular in cultured fibroblasts, suggested that ultrastructural lesions might also accompany hexosaminidase A deficiency in cultured fibroblasts. Electron microscopic studies on six human skin fibroblast lines and four amniotic fluid fibroblast lines, biochemically confumed to be deficient in hexosaminidase A, showed characteristic cvtoplasmic inclusions not observed in any normal lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1979
1979
1979
1979

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…It is classified as GM2-gangliosidosis type I because of its neuronal accumulation of GM2 ganglioside (1-3) and its asialo derivative (4), gangliotriaosylceramide (GgOsesCer). Since the publication by Klenk in 1939, it has been reported repeatedly that TSD is a clinically (5), morphologically (6,7), and genetically (8) well-defined entity, but its exact biochemical cause is evidently very complex. It has been observed that cultured skin fibroblast cells from TSD patients lack 3-D-hexosaminidase A (9), but these cultured cells do not accumulate GM2 ganglioside.…”
mentioning
confidence: 99%
“…It is classified as GM2-gangliosidosis type I because of its neuronal accumulation of GM2 ganglioside (1-3) and its asialo derivative (4), gangliotriaosylceramide (GgOsesCer). Since the publication by Klenk in 1939, it has been reported repeatedly that TSD is a clinically (5), morphologically (6,7), and genetically (8) well-defined entity, but its exact biochemical cause is evidently very complex. It has been observed that cultured skin fibroblast cells from TSD patients lack 3-D-hexosaminidase A (9), but these cultured cells do not accumulate GM2 ganglioside.…”
mentioning
confidence: 99%